The Effectiveness of Coal-Based Organic Fertilizer and Cow Manure on Yield Quality of Several Tomato Varieties (Lycopersicum esculentum L.) - Made Sri Yuliartini; I Gusti Made Arjana; Ida Bagus Komang Mahardika (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2021)
Tomato is an important vegetable crop and has been widely cultivated as a garden plant or commercially. The purpose of this study was to measure the effectiveness of organic fertilizer based on coal and cow dung based on several tomato varieties. This study used a factorial randomized design with two factors, namely the type of fertilizer consisting of